2014
DOI: 10.1155/2014/702807
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio: Novel Markers for Diagnosis and Prognosis in Patients with Idiopathic Sudden Sensorineural Hearing Loss

Abstract: Background. We aim to provide useful evidence about the association of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) with idiopathic sudden sensorineural hearing loss (ISSNHL) and its possibility of emerging as a cheap, reliable, and independent prognostic marker of ISSNHL. Methods. 348 patients diagnosed with ISSNHL were included in our retrospective data analysis. Blood samples and the hearing assessments of the patients were carried out. Then, the patients were divided into 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
105
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 26 publications
4
105
2
4
Order By: Relevance
“…Mirvakili et al (2016) in a prospective case-control study showed no association between PC, MPV and PDW and occurrence of SSNHL; only PDW resulted correlated with the severity of hearing loss (p ¼ 0.043). On the contrary, Sagit et al (2013) and Seo et al (2014) analysing, respectively, haematological data of 31 and 348 SSNHL patients evidenced a significant difference in PC values between subjects with and without SSNHL. Furthermore, Yasan et al (2013), Wittig et al (2014), Quaranta et al (2015), Kum et al (2015) did not recognise PC as prognostic factor for hearing recovery (p40.05).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Mirvakili et al (2016) in a prospective case-control study showed no association between PC, MPV and PDW and occurrence of SSNHL; only PDW resulted correlated with the severity of hearing loss (p ¼ 0.043). On the contrary, Sagit et al (2013) and Seo et al (2014) analysing, respectively, haematological data of 31 and 348 SSNHL patients evidenced a significant difference in PC values between subjects with and without SSNHL. Furthermore, Yasan et al (2013), Wittig et al (2014), Quaranta et al (2015), Kum et al (2015) did not recognise PC as prognostic factor for hearing recovery (p40.05).…”
Section: Discussionmentioning
confidence: 78%
“…In particular, Seo et al (2014) and Kum et al (2015) showed lower values of lymphocyte count in patients with less than 15 dB HL of hearing gain with respect to the initial hearing loss. Masuda et al (2012), _ Ikinciogullar{ et al (2014) and Quaranta et al (2015) instead did not observe any correlation between lymphocyte count and recovery rate.…”
Section: Discussionmentioning
confidence: 82%
“…39 Sudden sensorineural hearing loss, Bell's palsy and vestibular neuritis are certain pathological conditions that have been found to be related to NLR and PLR in otolaryngological practice. [40][41][42] Mean platelet volume (MPV) is a blood marker related to function and activation of platelets. 43 A study on patients with stroke reported that NLR increase and CRP (C reactive protein) which is an inflammation marker are significantly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the platelet-to-lymphocyte ratio (PLR) has been to be related to a poor prognosis in patients with peripheral arterial disease [5] . There are studies in the literature that show a relationship between SHL prognosis in adults and the NLR and PLR [6] .…”
Section: Introductionmentioning
confidence: 99%